(untitled) (Andamios, Revista de Investigación Social, 2009)
This article addresses the conflicting relationship between Urban Heritage and Cultural Tourism in Mexico City, with special focus on two emblematic sites recognized as World Heritage. We firstly analyze the dispute on the use of cultural heritage, collective by definition, which has become an important tourist activity (the third largest source of income in the country). Then we discuss the public policies that, since the 1990s, have mainly encouraged tourism, leisure and cultural consumption over the socio-economic problems in those territories. These policies threaten to turn Xochimilco into a thematic Park, and a portion of the Historic Center into an enclave for tourism and new high-income residents.